The Effectiveness of Numbered Head Together in Learning - Saptono, Bambang (Jurnal Prima Edukasia, 2024)
Elementary school teachers frequently encounter the challenge of achieving suboptimal learning gains. This research intends to characterize student learning outcomes before and after implementing the NHT Cooperative Learning Model and assess the impact of the Numbered Head Together Cooperative Learning Model on elementary school student learning outcomes. This research is a type of quasi-experimental research using a quantitative approach. The sample in this study was 15 elementary school students at the Class IV level obtained from the target class in elementary school. Data collection was carried out using learning outcomes tests and observation techniques. The data analysis technique used is descriptive and inferential statistical analysis via the t-test. The research results show a significant influence of the Numbered Head Together Cooperative Learning Model on student learning outcomes.